Respostas

2014-01-13T12:30:18-02:00
(x+4)*(x-5)=5x-16
x²-5x+4x-20=5x-16
x²-x-5x-20+16=0
x²-6x-4=0

Δ= (-6)²-4*1*(-4)
Δ= 36+16
Δ= 52

x= 6±√Δ/2

x=6±√52/2

x'=6+7,21/2
x'= 13,21/2  ~ x'= 6,60

x''= 6-7,21/2
x''= -1,21/2  ~x''= -0,60
sendo assim coloco o x' e x'' com a raiz quadrada de 52 msm assim?
:)
Vai ficar como fiz :)
^.^
Comentário foi eliminado
2014-01-13T12:39:50-02:00
(x+4).(x-5)=5x-16
x²-5x+4x-20= 5x-16
x²-x-20-5x+16=0
x²-x-5x-20+16=0
x²-6x-4=0

a= 1 b=-6 c= -4
Δ= 36 - (-16)
Δ= 52

x= 6 +/-
√52/2
x= 6+/- 2√13/2
x'= 3+2√13
x''= 3-2√13
1 5 1